2004
DOI: 10.1024/0300-9831.74.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Folate status of adults living in the Canary Islands (Spain)

Abstract: Even though nutritional folate status can be considered minimally acceptable, it may reflect the low level of fruit and vegetable consumption within the Canary Islands population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…Lower serum folate, erythrocyte folate and serum vitamin B12 levels in smokers, compared with those of non-smokers, may be the cause of their reduced plasma homocysteine concentration (Ganji and Kafai, 2003). Although in previous research (Henríquez et al, 2004) we found lower plasma levels of these vitamins among smokers, this was not the case with homocysteine.…”
Section: Discussioncontrasting
confidence: 49%
“…Lower serum folate, erythrocyte folate and serum vitamin B12 levels in smokers, compared with those of non-smokers, may be the cause of their reduced plasma homocysteine concentration (Ganji and Kafai, 2003). Although in previous research (Henríquez et al, 2004) we found lower plasma levels of these vitamins among smokers, this was not the case with homocysteine.…”
Section: Discussioncontrasting
confidence: 49%
“…[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] In addition, other factors not considered by many investigators include differences in the specific type of hormone used in the OCs, 58,59 compliance with the OC regimen, 44,58,59 and duration of OC use. 50,58 Folate status in these earlier studies was, in most cases, based solely on a comparison of serum folate concentration between groups of OC users and non-users. In addition, conclusions relative to the impact of OC use on folate status would have been strengthened if red blood cell (RBC) folate concentration would also have been measured, since this folate status indicator reflects liver folate concentration and thus body stores.…”
Section: Folatementioning
confidence: 99%
“…For example, in most studies there were no controls for dietary folate intake, vitamin supplement use, smoking, or alcohol use 39–57 . In addition, other factors not considered by many investigators include differences in the specific type of hormone used in the OCs, 58,59 compliance with the OC regimen, 44,58,59 and duration of OC use 50,58 . Folate status in these earlier studies was, in most cases, based solely on a comparison of serum folate concentration between groups of OC users and non‐users.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The specific methodology has been published elsewhere 19 . In order to assess the adherence to an MD pattern, a specific score was calculated, based on ten food items.…”
mentioning
confidence: 99%